2021
DOI: 10.7554/elife.61313
|View full text |Cite
|
Sign up to set email alerts
|

The SWELL1-LRRC8 complex regulates endothelial AKT-eNOS signaling and vascular function

Abstract: The endothelium responds to numerous chemical and mechanical factors in regulating vascular tone, blood pressure and blood flow. The endothelial volume regulatory anion channel (VRAC) has been proposed to be mechano-sensitive and thereby sense fluid flow and hydrostatic pressure to regulate vascular function. Here, we show that the Leucine Rich Repeat Containing Protein 8a, LRRC8A (SWELL1) is required for VRAC in human umbilical vein endothelial cells (HUVECs). Endothelial LRRC8A regulates AKT-eNOS signaling u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 99 publications
6
49
0
Order By: Relevance
“…In this study (Figure 6), AKT, iNS, eNOS, and MAPK were downregulated in the model group compared with the control group and significantly upregulated in the GP and MET groups compared with the model group. These results were in line with the data presented in previous reports (Alghanem et al, 2021;Cheng et al, 2021). As reported, the AGE-RAGE signaling pathway is closely associated with T2DM and inflammation (Syed et al, 2020).…”
Section: Regulation Of Pi3k/akt and Age-rage Signaling In Vivosupporting
confidence: 93%
“…In this study (Figure 6), AKT, iNS, eNOS, and MAPK were downregulated in the model group compared with the control group and significantly upregulated in the GP and MET groups compared with the model group. These results were in line with the data presented in previous reports (Alghanem et al, 2021;Cheng et al, 2021). As reported, the AGE-RAGE signaling pathway is closely associated with T2DM and inflammation (Syed et al, 2020).…”
Section: Regulation Of Pi3k/akt and Age-rage Signaling In Vivosupporting
confidence: 93%
“…The identification of the LRRC8 gene family has revitalized the VRAC field, by confirming previously suspected roles and discovering new roles in adipocyte physiology, insulin signaling, vascular physiology, sperm development, drug uptake, immune responses to virus infection, and neurotransmitter release in the brain (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Many of these studies have highlighted the need for developing potent and specific pharmacological tools for probing the physiology and therapeutic potential of VRAC in human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Hypotonic swelling has been shown to promote the release of NO and reactive nitrogen oxide species in various cells ( Kimura et al, 2000 ; Haussinger and Schliess, 2005 ; Takeda-Nakazawa et al, 2007 ; Kruczek et al, 2009 ; Gonano et al, 2014 ) and to augment LPS-triggered iNOS expression in RAW 264.7 macrophages ( Warskulat et al, 1998 ). Recently, it has been shown that in HUVECs, VRAC/SWELL1/LRRC8A mediates endothelial cell alignment via stretch-dependent Akt-eNOS signaling and formation of a signaling complex made up by Grb2, Cav-1, and eNOS ( Alghanem et al, 2021 ).…”
Section: Water Ions and Their Channels And Transporters In Pinocytosismentioning
confidence: 99%
“…LRRC8A-E/SWELL1 proteins are essential components of the volume-regulated outwardly rectifying Cl – current (VRAC, VSOR, VSOAC, ICl swell , ICl vol ) elicited in most cells during cell swelling ( Qiu et al, 2014 ; Voss et al, 2014 ; Jentsch, 2016 ; Jentsch et al, 2016 ; Okada, 2020 ; Bertelli et al, 2021 ), and they are involved in a broad variety of cellular functions ( Chen et al, 2019 ). LRRC8A-E/SWELL1 also regulate the PI3K-Akt, Erk1/2, mTOR signaling cascade ( Kumar et al, 2020 ; Alghanem et al, 2021 ). Recently, Li et al (2020) demonstrated the expression of LRRC8 family members on lysosomal membranes and their ability to build functional lysosomal VRACs (Lyso-VRACs).…”
Section: Water Ions and Their Channels And Transporters In Pinocytosismentioning
confidence: 99%